The molecular biology and biotechnology of flowering (CABI, 2006)
This is the second edition of the book first published in 1993 with a title of "The Molecular Biology of Flowering." It expands and updates the current knowledge of the molecular mechanisms of flowering and shows how molecular biology and the opportunities of biotechnology have made major progress when applied to flowering. It includes new chapters and others substantially revised and updated. Topics such as the evolution of flowers, floral senescence and apomixis are included in this new edition. The 13 chapters of this book are presented in the following sections: external and internal regulation of flowering (3 chapters); floral development (6 chapters); and fertilization and gametophyte development (4 chapters). The book is intended for research workers and advanced students in plant molecular biology and developmental biology, from both pure and applied (agricultural and horticultural) perspectives.